2020
DOI: 10.3390/cancers12092650
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oils and Their Main Chemical Components: The Past 20 Years of Preclinical Studies in Melanoma

Abstract: The last two decades have seen the development of effective therapies, which have saved the lives of a large number of melanoma patients. However, therapeutic options are still limited for patients without BRAF mutations or in relapse from current treatments, and severe side effects often occur during therapy. Thus, additional insights to improve treatment efficacy with the aim to decrease the likelihood of chemoresistance, as well as reducing side effects of current therapies, are required. Natural products o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 265 publications
(374 reference statements)
0
16
0
Order By: Relevance
“…At present, EOs are used to ameliorate cancer patients’ quality of life and clinical trials are ongoing to evaluate their efficacy or the efficacy of their components in cancer patients (NCT02336087, NCT03449303, NCT04560114, NCT04449315, NCT00003219, NCT00003238, NCT01459172, NCT01046929, NCT04296266). From the hundreds of studies published in the last years, it is evident that, in addition to their chemopreventive effects, several EOs and their constituents show antioxidant, antiproliferative, proapoptotic, antiangiogenic, and antimetastatic activity in melanoma models 21 23 . Synergistic effect of EO components such as geraniol 24 , 25 , β-elemene 26 , 27 , β-caryophyllene 28 , limonene 29 , eugenol 30 , and thymoquinone 31 , 32 with cancer therapy has been also reported.…”
Section: Introductionmentioning
confidence: 99%
“…At present, EOs are used to ameliorate cancer patients’ quality of life and clinical trials are ongoing to evaluate their efficacy or the efficacy of their components in cancer patients (NCT02336087, NCT03449303, NCT04560114, NCT04449315, NCT00003219, NCT00003238, NCT01459172, NCT01046929, NCT04296266). From the hundreds of studies published in the last years, it is evident that, in addition to their chemopreventive effects, several EOs and their constituents show antioxidant, antiproliferative, proapoptotic, antiangiogenic, and antimetastatic activity in melanoma models 21 23 . Synergistic effect of EO components such as geraniol 24 , 25 , β-elemene 26 , 27 , β-caryophyllene 28 , limonene 29 , eugenol 30 , and thymoquinone 31 , 32 with cancer therapy has been also reported.…”
Section: Introductionmentioning
confidence: 99%
“…However, although the significant clinical progress due to these therapeutic approaches, MM is still incurable as it is associated with high rates of recurrence and poor prognosis. In addition, the observed side effects caused by systemic toxicity, along with drug resistance, can further contribute to the limited therapeutic efficacy against MM [ 6 , 11 , 15 ]. To this end, the development of new therapeutic approaches is of high importance in order to improve current existing protocols, thereby improving the quality of life in MM patients [ 6 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, some linalool derivatives were identified, as linalool oxides and lilac aldehydes, that could have improved cytotoxicity of the studied Eos against K562. Perillyl alcohol is a well‐known angiogenic compound and can enhance the cytotoxicity of other drugs through synergistic effects [52] . Yan and Dong showed that this alcohol enhanced the inhibitory effects of the designed 2‐phenylaminopyrimidine STI571 against the growth of K562 cancer cell lines [53] .…”
Section: Resultsmentioning
confidence: 99%